Correlation of Public Self-Awareness with Behaviour in Suppressing the Spread of COVID-19 at Parombunan Sub Disctric Zone VI Sibolga City in 2021 - Samfriati Sinurat; Ice Septriani Saragih; Maya Febriayu Larosa (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2021)
Self-awareness is a concern for oneself and readiness to recognize oneself for what is done. Self-awareness is a must-have behavior to prevent transmission COVID-19 his study aims to determine the correlation of public self-awareness with behaviour in suppressing the spread of covid-19 at parombunan sub disctric zone vi sibolga city in 2021. The type of research design used is correlational with research design cross sectional with the sampling method is accidental sampling as many as 77 respondents at parombunan sub disctric zone vi sibolga city in 2021. The instrument used in data collection is a questionnaire sheet. Data analysis using alternative test fisher exact. The results showed  that 70 people (90.9%) have good self-awareness and 70 people (90.9%) have  good behavior. The results of the testfisher exact obtained p-value = 0.014 (p > 0.05). This shows that there is a relationship between community self-awareness and behavior in suppressing the spread of COVID-19 at parombunan sub disctric zone VI  sibolga city in 2021. The Conclusion of this study is there is a correlation of Public Self-Awareness with Behaviour in Suppressing the Spread of COVID-19 at Parombunan Sub Disctric Zone VI Sibolga City in 2021 t is hoped that the respondents can improve their self-awareness so that they can better implement behaviors in suppressing the spread of COVID-19 at parombunan sub disctric zone VI sibolga city in 2021.